Improving marketing skills through logo design training for the local business community - Fadhli Ranuharja; Wiwik Indrayeni; Agariadne Dwinggo Samala; Abdul Hasim; Chintiya Larashati; Yose Indarta (Journal of Community Service and Empowerment, 2023)
Sangir Regency which is located in South Solok Regency, West Sumatra, Indonesia is potential for culinary tourism because the data obtained by the number of local entrepreneurs in the Sangir Nagari Sungai Kunyit area reveal that several communities of local entrepreneurs engaged in home-based culinary businesses. The lack of use of technology to grow the selling value of regional products is an obstacle for local business communities to develop their businesses. Local entrepreneurs lose competitiveness if they want to market their products more broadly. The demographic location of Nagari Sungai Kunyit, which is quite far from the city of Padang Aro, also makes the inclusion of marketing trend technology not well utilized by the community. The method used in this service activity is the following: the first step was preparation, including observation and licensing administration; the second step was training in a 2-day successive workshop; the third step was 1-day evaluation; and the last step was product marketing assistance through the UNP Faculty of Tourism and Hospitality. The existence of skills development training activities has succeeded in increasing the resources of the local Nagari Sungai Kunyit business community in the field of making logos, which have become reinforcements, providing added value to the products produced. Furthermore, it helps small entrepreneurs to make products more attractive because they have the characteristics of their respective logos. Increasing human resources in the field of branding design is expected to spur an increase in the people's economies in South Solok Regency. It is proven that this activity has increased local business sales turnover and entrepreneurs are more confident in marketing their products outside the region.